Making Sense of Aborignial Educare-Givers' Identities - Su-Chen Chang (National Taipei University of Education, 2015)
This study attempts to explore the sense-making process of aboriginal educare-givers' identities through narrative inquiry. The materials for analysis include interactivenarrative field texts, narrative- interview field texts, researcher's journals, and interviews' transcripts. The findings are as follows: The aboriginal identity is fluid. The ethnic identity and educare-giver identity develop in two parallel lines. And self-narrative is the pathway to seek their culture, and promote aboriginal educare-givers' identities. Further, this study has deconstructed the author's own identity as "teacher and researcher", suggesting professors in teacher preparation programs to: see students through different lenses in terms of their ethnicity, transgress between teaching and researching, and practice narrative analysis in the eyes of an educare-giver. Finally, suggestions are offered for teacher education programs as well as individual aboriginal educare-givers seeking and balancing between different identities.